Effects of COVID-19 home confinement on eating behavior: A review - Eman S. Alamri (SAGE Publishing, 2021)
Coronavirus disease is a global pandemic that has led to radical changes in lifestyle habits, including dietary habits. Therefore, the objective of the present review is to evaluate the effect of quarantine on dietary habits when enforcing a lockdown. Some databases were used, including Web of Science, Science Direct, Google Scholar, and PubMed. Ten studies conducted between March and May 2020 were included. There is an increase in the number of meals and snacks during home confinement as well as unhealthy food such as fast food, sweets and chocolate, sugar-added drinks, and processed meat, while fruit and vegetable consumption was reduced. Very few studies reported that participants had increased fruit and vegetable intake. In conclusion, collateral effects of this pandemic include an environment that is not favorable to healthy dietary habits, which could have a lasting impact on health. The long-term health effects are unknown and worth investigating.